2013
DOI: 10.1159/000353252
|View full text |Cite
|
Sign up to set email alerts
|

Facial Affect Recognition Performance and Event-Related Potentials in Violent and Non-Violent Schizophrenia Patients

Abstract: We investigated whether male inpatients with schizophrenia and a history of hands-on violent offences (forensic schizophrenic, FOS) are more impaired in emotion recognition than matched schizophrenia patients without any history of violence (general psychiatric schizophrenic, GPS). This should become apparent in performance in psychometry and in scalp event-related brain potentials (ERPs) evoked by pictures of facial affect. FOS and GPS (each n = 19) were matched concerning age, intelligence, comorbid addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…Our participants were similar in profile to participants in previous studies of social cognition in forensic patients (Pinkham et al;Frommann et al, 2013;Luckhaus et al, 2013).…”
Section: Limitationssupporting
confidence: 69%
“…Our participants were similar in profile to participants in previous studies of social cognition in forensic patients (Pinkham et al;Frommann et al, 2013;Luckhaus et al, 2013).…”
Section: Limitationssupporting
confidence: 69%
“…Among patients with schizophrenia, the risk for violence has been associated with several factors, such as personality traits, substance abuse, intelligence, presence of psychotic symptoms, and demographic background (86). To the best of our knowledge, there is only one study assessing salience in forensic patients: greater impairment in affect recognition performance combined with higher salience and arousal may contribute to the occurrence of violent acts in schizophrenic patients (87). Additionally, it has been demonstrated that positive symptoms in schizophrenic patients can be associated with a criminal history even before diagnosis of a first episode (88).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in identification of spoken emotions (semantics and prosody) for people with schizophrenia were associated with impaired social functioning (56,57). However, to the best of our knowledge, the literature is silent regarding identification of spoken emotions by forensic patients with schizophrenia.…”
Section: Identification Of Emotions In Forensic Patients With Schizopmentioning
confidence: 99%